Message from ACHSM President - Dr Neale Fong - Neale Fong (ACHSM, 2021)
I trust that you are well and as a leader or manager in the health sector wherever you are, you have taken time to ensure your own health and wellbeing in these extraordinary times. There is no more important time than now to ensure that you have the resilience and reserves to travel through these uncertainties. In the last issue this column focussed on the ACHSM's Certification Program and the importance of a credential for health leaders and executives. As I noted then, certification in a profession is an employment currency within the health sector that has traditionally excluded the leaders and managers. Through the introduction of these credentials, the College supports members and future members to have their body of knowledge and skills recognised and provides the platform for continuing development. Today let me focus on the importance of lifelong learning and intentionally managing a career that hopefully will span decades, providing you with personal satisfaction and success. Committing to lifelong learning, as we mandate within Certification, is a commitment to your own development, and your own sense of staying curious and active within the profession. A quiet and consistent focus on staying current is at the foundation of confident and competent leadership and ACHSM sees this as being at the heart of our offerings to College members.